Multi-Criteria Decision Making Framework for Sustainable Urban Drainage System Design Considering Climate Change Resilience and Water Quality Impacts - Ulfa Nadia; Dara Tursina; Chicha Rizki Gunawan (International Forum of Researchers and Lecturers, 2024)
Urban drainage systems face mounting pressure due to the combined impacts of rapid urbanization and climate change. The expansion of impervious surfaces and altered precipitation patterns contribute to increased stormwater runoff, exacerbating flood risks and water quality issues in cities. Traditional drainage systems, focused primarily on controlling water volume, are insufficient to address the growing complexity of urban drainage challenges. This study proposes Sustainable Urban Drainage Systems (SUDS) that integrate flood management, water quality improvement, and climate resilience. By incorporating nature-based solutions such as permeable pavements, green roofs, and rain gardens, these systems aim to reduce runoff, enhance groundwater recharge, and mitigate the negative effects of urbanization. Through a Multi-Criteria Decision Making (MCDM) framework, this research evaluates various drainage solutions based on technical, socio-economic, and environmental criteria. The findings indicate that SUDS outperforms traditional systems in flood mitigation, water quality control, and climate resilience, highlighting their importance in adapting to changing climatic conditions. This paper emphasizes the need for sustainable drainage solutions to ensure long-term urban resilience and improve the overall quality of urban environments.